Kedudukan Kreditur Pemegang Hak Tanggungan Pasca Musnahnya Objek Hak Tanggungan Menurut Perspektif Hukum Kepailitan - Merada, Made Bhisma Abidharma; Swardhana, Gde Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 01 (2024), 2024)
This research aims to understand the position of creditors holding mortgage rights from the perspective of bankruptcy law after the object of the mortgage rights they hold has been destroyed. This scientific article is normative legal research. In an effort to answer the problems in this research, a conceptual approach and a statutory approach were used. Based on the research conducted, it was found that the destruction of the object of mortgage rights resulted in the abolition of mortgage rights so that the mortgage rights certificate that had been issued lost its executorial power. However, debtors cannot be separated from their obligations to pay off their debts to creditors. Apart from that, creditors holding mortgage rights who were originally separatist creditors have had their position degraded to become concurrent creditors because they have lost their material collateral as a result of the deletion of mortgage rights.